Mode I cohesive zone model for delamination in composite beams - Morais, A. B. de (2013)
A cohesive zone model was developed for mode I delamination in composite beams. The present model is an extension of a beam on elastic foundation analysis similar to the one that led to the well-known corrected beam theory data reduction scheme. In particular, it is demonstrated that the shear foundation considered in most formulations can actually be discarded, thereby allowing a much simpler model implementation. The present model agrees very well with finite element analyses of double cantilever beam and moment-loaded double cantilever beam specimens with a wide range of properties.